Impact of micro determinants on household health and poverty in Nigeria - Yakubu, Yahaya (2018)
Health and wealth of a nation have been identified by various studies as important components of national development. Hence, they feature in different global development agenda such as the recently concluded Millennium Development Goals (MDGs) in 2015 and the current Sustainable Development Goals (SDGs). In the MDGs, developing countries were left behind and are also unlikely to achieve the SDGs, hence, the need for multi-sectoral approach to expedite actions towards achieving the SDGs. Nigeria as a developing country is not an exception in this need. This study therefore explore the impact of micro determinants on population health outcomes, reproductive health, and extreme poverty in Nigeria, being three major focal points in the SDGs. The study uses national representative cross sectional data from the 2013 Nigeria Demographic and Health Survey, and employs the Logistic Regression Model to study the effect of the micro determinant on maternal mortality, under-5 mortality, unmet need for family planning, and extreme poverty in Nigeria. Findings of the study reveal significant association between micro determinants and population health outcomes, reproductive health, and extreme poverty. Higher fertility and women decision making power in the household significantly increases and decreases the likelihood of maternal mortality, respectively. Parent’s education and exposure to media are significant factors in reducing the likelihood of under-5 mortality, while on the contrary, fertility index (parity), short preceding birth interval, no access to electricity, and unimproved sanitation significantly increase the chances of a child dying before its fifth birthday. Women and under-5 children in the northern region and of Hausa/Fulani extraction are more prone to maternal and under-5 mortality, respectively. Couple’s education, exposure to family planning messages, family planning counselling, and women household decision making power significantly reduce the likelihood of unmet need for family planning. Couple’s fertility measures (number of living children, desires for more children, ideal number of children, and polygyny) significantly increase the likelihood of a woman having unmet need for family planning. Women in the northern part and of Hausa/Fulani tribe are more likely to have unmet need for family planning. Men and women’s education and women household decision making power are significant important factors in reducing extreme poverty in the household. Higher fertility measured by number of household’s members, no electricity, unimproved source of drinking water and sanitation increases the likelihood of extreme poverty. Households in the northern part and of Hausa/Fulani extraction are more likely to be extremely poor. The study conclude that the worsening situation of population health outcome, reproductive health, and extreme poverty in Nigeria are associated with micro factors at individual and household levels. It therefore recommends that more policy attention and awareness campaign should be directed to addressing the relevant micro determinants at individual and household levels for timely achievement of the SDGs’ health and poverty goals in Nigeria, and other national development health and poverty goals.